Meteorological factor contributions to the seesaw concentration pattern between PM2.5 and O3 in Shanghai - Sun, Yongzhao; Wang, Xiaoyan (Frontiers in Environmental Science, 2022)
With the implementation of various stringent emission reduction measures since 2013 in China, significant declines in fine particle (PM2.5) concentrations have occurred nationwide. However, China has suffered from increasing levels of ozone pollution in eastern urban areas. Many studies focus on the chemical interaction between PM2.5 and O3, but the meteorological mechanisms of the seesaw variation pattern between them are still unclear. Taking the megacity Shanghai (SH) as an example, we explored the meteorological causes of two types of PM2.5-O3 concentration variation seesaw events, i.e., high PM2.5 concentration with low O3 concentration (Type-one) events and low-PM-high-O3 (Type-two) seesaw events. To show the origins of air masses arriving at SH, 2-day backward trajectories were computed and clustered every 6 h using the HYSPLIT backward trajectory model. The backward trajectories of the 144 Type-one events are divided into three clusters. Among the three clusters of Type-one seesaw events, the boundary layer height decreases by 20.53% to 53.58%, and the wind speed decreases by 17.99% to 28.29%, which is unfavorable for the diffusion of local air pollutants and contributes to the accumulation of PM2.5. The increase in cloud cover and relative humidity and the decrease in shortwave radiation promote the hygroscopic growth of aerosols and suppress the production of O3. Additionally, a backward air mass with a high content of PM2.5 also plays an important role in the Type-one event, especially in the case of cluster one. In terms of the Type-two seesaw event, O3-rich air masses from the nearby east sea surface and remote northeast China increase the local O3 of SH. A significant decrease in cloud cover and increase in solar radiation are favorable for the photochemical production of ozone. Moreover, high boundary layer depth and wet deposition contribute to the decrease in PM2.5 concentration. The results will provide suggestions for the government to use to take measures to improve the air quality of SHs.